Trade policy-making process level one of the two level game : country studies in the Western Hemisphere (IDB WashingtonUS, 2002)
Reports the results of a project on trade policy-making in eight Western Hemisphere nations. Focuses on the question of how best to accomodate the participation of non-state actors in the formulation of national trade policies and negotiating agendas.
Bibliography: p. 91